IMPROVING STUDENTS’ READING COMPREHENSION ON DESCRIPTIVE TEXT THROUGH CSR (COLLABORATIVE STRATEGIC READING) - Subekti, Wening; Arifin, Zainal; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: This research aims to know whether the process of CSR can improve students’ reading comprehension on descriptive text to the Eleventh Grade Students of SMA Negeri 1 Singkawang. The research method used is a Classroom Action Research. The study sample is 35 students. Based on the analysis of  the  data, the mean score in the first cycle was 76,2 which was categorized as good and in the second cycle was 88 which was categorized as excellent. The result of the students’ mean score reached 99% of standard minimum score. It can be concluded that CSR can improve students’ reading comprehension on descriptive text.   Keywords: CSR, Reading Comprehension, Descriptive Text Abstrak: Penelitian ini bertujuan untuk mengetahui apakah proses CSR dapat meningkatkan pemahaman membaca siswa pada teks deskriptif untuk siswa kelas XI SMA Negeri 1 Singkawang. Metode penelitian yang digunakan adalah penelitian tindakan kelas. Sampel penelitian adalah 35 siswa. Berdasarkan analisis data, nilai rata-rata pada siklus I adalah 76,2 yang dikategorikan baik dan pada siklus II adalah 88 yang dikategorikan sangat baik. Hasil nilai rata-rata siswa mencapai 99% dari standar nilai minimum. Dengan demikian dapat disimpulkan bahwa CSR dapat meningkatkan pemahaman membaca siswa pada teks deskriptif.   Kata Kunci: CSR, pemahaman membaca, teks deskriptif